2009
DOI: 10.1007/s11605-009-0881-z
|View full text |Cite
|
Sign up to set email alerts
|

ERCC1 and XRCC1 Gene Polymorphisms Predict Response to Neoadjuvant Radiochemotherapy in Esophageal Cancer

Abstract: Our data support the role of ERCC1 as a predictive marker for therapy response. Single-nucleotide polymorphisms of ERCC1 and XRCC1 could be applied to further individualize treatment strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 49 publications
1
38
1
1
Order By: Relevance
“…Our results suggest that T19007C SNP in the ERCC1 gene does not influence OS in our patients, in contrast to others, which found an association with response to platinum-based chemotherapy and survival in esophageal cancer, colorectal cancer, ovarian cancer and non-small cell lung cancer patients (17,(34)(35)(36). A proposed mechanism is that T19007C SNP may decrease ERCC1 mRNA stability and consequently, protein expression.…”
Section: Discussioncontrasting
confidence: 95%
“…Our results suggest that T19007C SNP in the ERCC1 gene does not influence OS in our patients, in contrast to others, which found an association with response to platinum-based chemotherapy and survival in esophageal cancer, colorectal cancer, ovarian cancer and non-small cell lung cancer patients (17,(34)(35)(36). A proposed mechanism is that T19007C SNP may decrease ERCC1 mRNA stability and consequently, protein expression.…”
Section: Discussioncontrasting
confidence: 95%
“…XRCC1 gene polymorphisms are reported to be correlated with the treatment outcome of cisplatin-based chemotherapy in several kinds of cancers, such as gastric cancer, colorectal cancer, nasopharyngeal cancer, ovarian cancer, pancreatic cancer, and esophageal cancer (Warnecke-Eberz et al, 2009;Giovannetti et al, 2011;Miao et al, 2012;Chen et al, 2013;Cao et al, 2014;Wu et al, 2014). Currently, several studies have reported the association between XRCC1 genetic polymorphisms and treatment outcome of advanced NSCLC (Yuan et al, 2006;Wang et al, 2004Wang et al, , 2008Sun et al, 2009;Li et al, 2011;Ke et al, 2012;Han et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…As a result of these studies, ERCC1 overexpression was suggested as an indicator of resistance against platin-based chemotherapies. Some cancers exhibit ERCC1 overexpression, as was shown with immunohistochemistry or RT-PCR [1,2].…”
Section: Introductionmentioning
confidence: 67%